Effectiveness of Trans Jateng Bus Rapid Transit (BRT) services for customers with disabilities in Surakarta city - Yunita Primasanti; Erna Indriastiningsih; Darsini Darsini (International Journal of Educational Research, 2024)
BRT Trans Jateng is a government mode of transportation that cannot be separated from the principle of good and quality public services for customers with disabilities. The aim of this research is to measure the effectiveness of Trans Jateng BRT services for customers with disabilities, especially in the city of Surakarta. The design of this research is to use the Fuzzy SERVQUAL method to measure the level of satisfaction of disabled customers with BRT Trans Jateng services. The sampling technique used was purposive sampling using 30 samples of disabled customers in the city of Surakarta. Here it can be seen that all of the five dimensions measured require improvement. Improvements are carried out based on the priority of the largest gap value. From the results of data processing, the first rank is the tangible dimension with a gap value of -2.0167, then the second rank is the empathy dimension with a gap value of -1.9583, the third rank is the responsiveness dimension with a gap value of -1.95, in the fourth rank is the assurance dimension with a gap value of -1.92, and the fifth rank of the reliability dimension with a gap value of -1.89